Revitalizing contaminated soils: The combined power of modified biochar and intrinsic bacteria for heavy metal and petroleum hydrocarbon removal and plants performance - Zahra Dianat Maharlouei; Davood Azadi; Majid Fekri (PLoS ONE, 2026)
Soil contamination with heavy metals and petroleum hydrocarbons poses a critical environmental challenge, threatening food security, human health, and ecosystem sustainability in various regions by reducing crop yields and introducing toxic pollutants into the food chain. Therefore, sustainable remediation strategies are essential to protect agricultural productivity. This study aimed to isolate native bacteria capable of degrading these contaminants from Kerman’s polluted soils and assess their synergistic effects with microbially modified biochar (MB) on soil bioremediation, quality enhancement, and maize performance. A total of 30 soil samples were collected from industrially contaminated sites in Kerman, Iran, and analyzed to isolate native bacterial species using biochemical and molecular tests. Biochars, prepared from rice husk and inoculated with the bacterial consortium, and were evaluated in a factorial greenhouse experiment. The experiment utilized a completely randomized design with 90 pots containing 4 kg of artificially contaminated soil (Cr, Pb, Cd, Cu; petroleum hydrocarbons) and four treatments: control, pristine biochar (PB), bacterial inoculants, and MB. Maize was grown for 90 days under controlled conditions, and soil and plant parameters, including physicochemical properties, contaminant levels, growth characteristics, transfer factor (TF), and bioaccumulation factor (BAF), were assessed. Five bacterial species ( P. fluorescens , R. qingshengii , B. metallica , B. cereus , S. pactum ) were isolated from 30 soil samples and tested with MB in a greenhouse experiment. Results showed MB reduced heavy metal bioavailability by 45–55% and hydrocarbons by 70% (p < 0.001), enhanced soil organic carbon, lowered metal uptake (e.g., TF for Cd: 0.27 vs. 0.95), and increased maize biomass (shoot: 30 g, root: 18 g vs. 15 g, 8 g, p < 0.001), offering a sustainable remediation strategy. These findings demonstrate the potential of integrating novel bacterial strains with modified biochar for effective, sustainable soil remediation for arid regions like Kerman, Iran.